2016
DOI: 10.1007/s00132-016-3302-5
|View full text |Cite
|
Sign up to set email alerts
|

Lornoxicam injection is inferior to betamethasone in the treatment of subacromial impingement syndrome

Abstract: Although a single subacromial lornoxicam injection provides rapid functional recovery, which partially extends into the intermediate term, its results are inferior to betamethasone and it may be an alternative only in patients where corticosteroids are contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition, Aksakal et al (18) investigated the effect of betamethasone injection and lornoxicam in performance of patients with shoulder impingement syndrome. They reported that a single dose of subacromial lornoxicam injection had a better improvement in comparison with betamethasone at the second week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Aksakal et al (18) investigated the effect of betamethasone injection and lornoxicam in performance of patients with shoulder impingement syndrome. They reported that a single dose of subacromial lornoxicam injection had a better improvement in comparison with betamethasone at the second week.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lornoxicam injection improved performance of patients faster. (18) In the above studies, it has been argued that NSAIDs respond better than corticosteroids. In contrast, in a study by Onat et al, they found that the kinesiotaping group and the corticosteroid group had a better range of motion than the NSAID group.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, although a single subacromial lornoxicam injection provides rapid functional recovery, which partially extends into the intermediate term, its results are inferior to betamethasone and it may be an alternative only in patients where corticosteroids are contraindicated. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) Although SIS is generally self-limiting, the cuff lesions and complications caused by SIS often exacerbate over time and lead to debility and decreased quality of life (QoL) of SIS patients. (3,4) Many conservative treatment modalities have been demonstrated to be bene cial in relieving subacromial in ammation and shoulder pain and improving the shoulder functional status in SIS, (5)(6)(7)(8) including systemic nonsteroidal anti-in ammatory drugs (NSAIDs), physical therapy, activity modi cation, electromagnetic radiation, therapeutic exercises, and corticosteroid injections. There is wide agreement that NSAIDs treatment is the rst choice for stage I or II SIS.…”
Section: Introductionmentioning
confidence: 99%